Avoidable Cancer Mortality in Germany Since Reunification: Regional Variation and Sex Differences - Westerman, Ronny; Mühlichen, Michael (Frontiers in Public Health, 2019)
Background: Regional comparisons of cancer-related mortality in Germany are traditionally focused on disparities between East and West Germany. Recent improvements in all-cause and cancer-related mortality show a diverse regional pattern beyond the known East-West mortality divide. A generalized approach of the avoidable/amenable cancer mortality definition is applied for suitable regional comparisons of long-term trends. Methods: Standardized death rates of preventable and amenable cancer mortality for men and women were computed for the period 1990–2014 to observe sex-specific excess mortality due to specific cancers after the German reunification. For regional comparison, three German super regions were defined in Eastern, Northwestern, and Southwestern Germany to account for similarities in long-term regional premature and cancer-related mortality patterns, socioeconomic characteristics, and age structure. Results: Since preventable and amenable cancer mortality rates typically have driven the recent trends in premature mortality, our findings underline the current regional pattern of preventable cancer mortality for males with disadvantages for Eastern Germany, and advantages for Southwestern Germany. Among women, the preventable cancer mortality has increased in Northwestern and Southwestern Germany after the German reunification but has decreased in Eastern Germany and converged to the pattern of Southwestern Germany. Similar patterns can be observed for females in amenable cancer mortality. Conclusions: Although the “traditional” East-West gap in preventable cancer mortality was still evident in males, our study provides some hints for more regional diversity in avoidable cancer mortality in women. An establishing north-south divide in avoidable cancer mortality could alter the future trends in regional cancer-related mortality in Germany.